The Vaccinia Virus G1L Putative Metalloproteinase Is Essential for Viral Replication In Vivo - Hedengren-Olcott, Marika (American Society for Microbiology, 2004)
The function of the putative metalloproteinase encoded by the vaccinia virus G1L gene is unknown. To address this question, we have generated a vaccinia virus strain in which expression of the G1L gene is dependent on the addition of tetracycline (TET) when infection proceeds in a cell line expressing the tetracycline repressor. The vvtetOG1L virus replicated similarly to wild-type Western Reserve (WR) virus in these cells when TET was present but was arrested at a late stage in viral maturation in the absence of TET. This arrest resulted in the accumulation of 98.5% round immature virus particles compared to 6.9% at a similar time point when TET was present. Likewise, the titer of infectious virus progeny decreased by 98.9% ± 0.97% when the vvtetOG1L virus was propagated in the absence of TET. Mutant virus replication was partially rescued by plasmid-encoded G1L, but not by G1L containing an HXXEH motif mutated to RXXQR. Modeling of G1L revealed a predicted structural similarity to the α-subunit of Saccharomyces cerevisiae mitochondrial processing peptidase (α-MPP). The HXXEH motif of G1L perfectly overlaps the HXXDR motif of α-MPP in this model. These results demonstrate that G1L is essential for virus maturation and suggest that G1L is a metalloproteinase with structural homology to α-MPP. However, no obvious effects on the expression and processing of the vaccinia virus major core proteins were observed in the G1L conditional mutant in the absence of TET compared to results for the TET and wild-type WR controls, suggesting that G1L activity is required after this step in viral morphogenesis.